Hydroxyapatite as a Biomimetic Alternative to Fluoride in Toothpaste Formulations: A Review - Gabrielle Callista Dwi Putri; Atiek Rostika Noviyanti; Yudha Prawira Budiman; Arie Hardian; Azman Bin Ma'Amor (Jurnal Kartika Kimia, 2026)
Hydroxyapatite (HA) has gained increasing attention as a biomimetic active ingredient in toothpaste due to its structural similarity to dental enamel and dentin, especially amid concerns over excessive fluoride exposure. This review discusses the role of HA in caries prevention and enamel remineralization, covering its antibacterial activity, physicochemical properties, synthesis strategies, and toothpaste applications. Evidence from in vitro, in situ, and clinical studies demonstrates that HA particularly in nano and ion-substituted forms effectively promotes enamel remineralization, enhances acid resistance, reduces dentin hypersensitivity, and exhibits antibacterial activity comparable or superior to fluoride toothpaste. However, challenges remain regarding nanoparticle stability, formulation consistency, and limited long-term clinical data. For HA to replace fluoride, it should be engineered as a reactive, well-dispersed nano-apatite (≤100 nm) with moderate-to-high crystallinity (~69–75%), stoichiometric Ca/P ratio of 1.67, and appropriate ionic substitution. Overall, HA represents a safe, biocompatible, and promising material for advanced toothpaste formulations.